2012
DOI: 10.7314/apjcp.2012.13.10.5213
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Breast Cancer Risk Levels and Health Beliefs of Women With and Without Previous Mammography in the Eastern Part of Turkey

Abstract: Objective: This research was conducted to determine the breast cancer risk levels of women with and without previous mammography and their beliefs on breast cancer and mammography. Methods: The sample for this descriptive research consisted of women aged 50 years or older who were registered at the Family Health Center in the city center of Erzurum. The research was conducted with a total of 420 women with at least one mammography (210) and without mammography (210) who presented to the center on Wednesdays an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…According to a study from eastern Turkey, scores for susceptibility, severity, health motivation, and mammography benefits were higher, and mammography barrier scores were lower in women who had mammography as compared to those who did not undergo mammography (66).…”
Section: Discussionmentioning
confidence: 99%
“…According to a study from eastern Turkey, scores for susceptibility, severity, health motivation, and mammography benefits were higher, and mammography barrier scores were lower in women who had mammography as compared to those who did not undergo mammography (66).…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, lack of knowledge is one important reason for dealy in treatment (Rastad et al, 2012). So, it would be useful design of interventions proposed at breast cancer prevention through improved women's awareness on breast cancer and screening and or enhanced screening, especially in those without any experience of mammography (Baysal and Polat, 2012).. We thus conducted this study to describe Iranian women's perception of breast cancer and screening.…”
Section: Introductionmentioning
confidence: 99%
“…Schwab et al (14) reported that better results were achieved regarding tumor size, disease phase and histological examination through screening programs in women with breast cancer. In a study conducted in Turkey (15), groups having higher risk for breast cancer had mammography rates 11 times higher than the others and in another study, it was determined that the CBE rate was 48.1% in women with a family history (16).…”
mentioning
confidence: 99%